Thermal pyrolysis of LDPE and LLDPE films in post-consumer packaging - Vallada, Douglas da Silva; Moraes, Carlos Alberto Mendes; Silva, Paulo Ricardo Santos da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
Thermoplastics are increasingly present in the daily life of society in the most varied applications. Among the thermoplastics, polyethylene is the one that presents the higher volume of worldwide production and consumption. However, a large part of its applications are for products with a short shelf life, especially the food packaging sector. This way, they become expressive constituents in the composition of urban solid waste, leading to large quantities often being deposited in landfills. Pyrolysis appears as a technology for recycling plastic waste, allowing the recovery of the monomers that originated it. Through this thermochemical process, the waste is converted into three different products: oil or, in some cases wax, non-condensable gases, and a solid fraction named char. Thus, the goal of this study is to contribute for the development of pyrolysis as a technology for the final treatment of low-density polyethylene (LDPE) and linear low-density polyethylene (LLDPE) waste from post-consumer packaging, through the analysis of the influence of the pyrolysis temperature in the chemical composition of the oil produced, as well as the discussion of possible applications. For this purpose, the waste was initially characterized through analyses of attenuated total reflectance Fourier-transform infrared spectroscopy (ATR-FTIR), thermogravimetry (TGA), differential scanning calorimetry (DSC), and X-ray fluorescence (XRF). The characterization experiments showed that the plastic waste is constituted of 4.07% ash, 0.52% fixed carbon, and 95.54% volatile matter, showing its great potential to produce pyrolytic oil. Thermal degradation of the waste initiated at around 410°C and continued through about 530°C, with maximum rate of thermal degradation at about 488°C. The pyrolysis process was carried out with 50g samples of post-consumer LDPE and LLDPE, previously agglutinated, with particle size ranging from 0.001mm to 4mm, in a horizontal quartz reactor, with an inert atmosphere of N2, heating rate of 10°C/min, and residence time of 30 minutes. The experiments were conducted with experimental temperatures of 500°C and 700°C, in order to verify the influence of the temperature in the chemical composition of the oil obtained in the process. The analysis of the oil collected at 500°C by infrared spectroscopy revealed a specter similar to the one of commercial diesel. Through gas chromatography coupled with mass spectrometry, it was verified a composition constituted mostly by olefins (44%), from 8 to 35 carbon atoms, followed by paraffins (23.8%), and cycloparaffins (10%). There was also a considerable percentage of alpha-olefins, important for the petrochemical industry, and a percentage of aromatic compounds on a trace level. By varying the temperature to 700°C, an increase in the level of aromatic compounds to 16.6% occurred, accompanied by a decrease in the percentage of olefins, paraffins, and cycloparaffins. The oils obtained in both temperatures have potential for application in steam cracking or conventional catalytic cracking processes to obtain the raw materials of the petrochemical industry.